Development of Canva-based Interactive Learning Media for Elementary School IPAS Learning - Fithrotin Nisyaa; Suratno; Susilo Tri Widodo (Postgraduate, University of Mataram, 2025)
This study aims to enhance the learning environment in elementary school IPAS (Integrated Science and Social Studies) classes by developing Canva-based interactive learning media. The focus is on making learning more engaging and effective, addressing issues with traditional teaching methods that can leave students feeling bored. The research employs the Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection instruments consist of pretests, posttests, and questionnaires to gather feedback from students and teachers. Expert validation results indicate that the learning media is very feasible, with material experts rating it at 92% and media experts at 96%. N Gain tests show significant improvement in student learning outcomes. Feedback from students and teachers is also highly positive, with 97.77% from small-group students, 97.08% from large-group students, and 100% from teacher. Based on the values obtained, canvas-based interactive learning media in elementary school IPAS learning can be said to have been developed that is feasible and effective to improve the learning outcomes of Class V students at SD Negeri Nongkosawit 02.